Prayer in the Old Testament - Russell, Douglas Godfrey (Rhodes University, Faculty of Divinity, Department of Divinity, 1972)
As "Prayer in the Old Testament" is a very wide subject, I have restricted myself to outlines on certain themes. In a sense the whole Bible can be described as "prayer" since it is a dialogue of man with God, and God with man. Obviously the word with which to attempt any definition of prayer is the Hithpa'el verb (?)and its noun (?). It describes speech with God. As the Hebrew poetic device of parallelism offers us synonyms to (?) we examine those words with much the same general definition. There are other words which the Hebrew concordance reveals as being translated as "prayer", or as describing prayer. Most of these words are the ordinary words for speech. The words for prayer, in general, describe speech before God. With this wide definition Chapter Two groups the various kinds of speech before God, and attempts to describe each. Prayer is seen as dialogue, as asking, and as praise and thanksgiving. Prayer, however, does not exist in a vacuum. It cannot be separated from the people who pray and the God who makes prayer possible. Personalities of prayer give prayer meaning, purpose and dynamic. Looking at their prayers in context enables us to grasp a little more fully the role of prayer in life itself. As God provides the framework of prayer we must also look at that framework. He determines what kind of prayers are acceptable. He gives direction and power to the words of prayer. Without God, prayer is either magic or meaningless words. In the final chapter I try to tie up some of the loose ends. Prayer is not just an isolated and individual thing it exists within the cult and the community. Certain disciplines accompany it.
Keywords: Bible -- Prayers; Worship in the Bible; Prayer